Kesetaraan Gender dan Strategi Nafkah untuk Penyusunan Program Penyuluhan pada Masyarakat Pesisir di Kabupaten Tanggamus, Provinsi Lampung - Helvi Yanfika; Begem Viantimala; Indah Nurmayasari; Abdul Mutolib (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluhan Pembangunan Indonesia), 2021)
This study aims to determine multiple livelihood strategies and collaboration for livelihood strategies and preparation of extension programs in the perspective of gender equality in fishing communities. The research method uses quantitative and qualitative approaches. The data were analyzed descriptively and statistically The research location is in Limau District Tanggamus Regency and the number of respondents was 80 fishermen. The data used are primary and secondary data. The results of this study indicate that the community applies a dual livelihood strategy and a collaborative livelihood strategy in Limau District consisting of On Farm strategy, On-Farm and Off-Farm, and On-Farm and Non-Farm. Cumulatively, the gender relations of fishermen's families in Limau District covering domestic, public and community activities have shown an equal division of labor between wives and husbands, namely 76.30 percent. Extension programs should aim at gender equality so as to increase their participation, access and control, as well as the benefits that women enjoy in developing coastal areas. Thus, the results of marine and fisheries development can touch all levels of society and bring society to prosperity and a better life.